2019
DOI: 10.4187/respcare.06978
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Lung Deposition From Nebulization Is Not Improved in the Lateral Decubitus Position in Healthy Volunteers

Abstract: BACKGROUND: Clinical benefits of inhaled therapies are related to the amount of drug deposited in the targeted area of the lung. Body positions that influence the distribution of lung ventilation should impact lung deposition of the nebulized drug. The aim of this study was to analyze the immediate effect of body position while the subject lies on his side (lateral decubitus) during nebulization on 3-dimensional total and regional lung deposition. METHODS: A randomized crossover trial was performed on healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…It is important to note that drug particles should be deposited in the lungs in a high enough proportion for the API to be absorbed and produce a therapeutic effect. Unsurprisingly, it has been shown that higher drug deposition in the lungs leads to enhanced clinical benefits [ 56 ]. As mentioned above, a common approach to improve the flow properties of powder for inhalation is to use carrier particles (such as lactose monohydrate).…”
Section: Challenges Associated With Drug Delivery To the Lungsmentioning
confidence: 99%
“…It is important to note that drug particles should be deposited in the lungs in a high enough proportion for the API to be absorbed and produce a therapeutic effect. Unsurprisingly, it has been shown that higher drug deposition in the lungs leads to enhanced clinical benefits [ 56 ]. As mentioned above, a common approach to improve the flow properties of powder for inhalation is to use carrier particles (such as lactose monohydrate).…”
Section: Challenges Associated With Drug Delivery To the Lungsmentioning
confidence: 99%